BABY & CHILD CARE - SPOCK, BENJAMIN (POCKET BOOKS DISTRIBUTING CO., MUMBAI, 1965)
In this book among the topics covered are- Discipline and spoiling, crying in early infancy, sleep problems, regular or demand schedules , breast feeding, twins, when you call the doctor.. and many more..
Keywords: CHILD PSYCHOLOGY